Sistem Pendukung Keputusan Kenaikan Jabatan Menggunakan Metode Profile Matching - Dian Nur Solihaningtias (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
With global information technology growing more rapidly, there are more and more people taking advantage of it to do their various activities or to solve their various problems. One of the problems is the filling of vacant positions in the promotion process that is often difficult to do due to the submission of candidates suitable for the positions by matching employee profiles and positions profiles is less thoroughly defined. To minimize the problem, a decision support system is needed to analyze some employees matching the existing position profiles. Profile Matching is conducted to make a recommendation on employees in the promotion and career planning systems by calculating sub criteria of each aspect (work attitude and intellectual capacity) consisting of 4 stages, namely GAP score calculation, core and secondary factor score calculation and total score and ranking calculation. The result of this study is a recommendation on employees with the highest score based on the calculation using the method.